The Use of 'The Saracen Opinion' on Knighthood in Medieval French Literature: L'Ordene de Chevalerie and L'Apparicion Maistre Jehan de Meun. (April 2016) - Çeçen, Zeynep Kocabiyikoğlu
This article aims to examine the differences and the similarities regarding the outlook on knighthood of two French poems, the anonymous Ordene de chevalerie, written sometime during the early thirteenth century, and Honoré Bovet's L'Apparicion maistre Jehan de Meun, written in the late fourteenth century. Whereas both works contain a Saracen figure who works as the agent conveying the state of Christian knighthood, the former gives an exalted portrait of Christian knighthood and the latter a critical one. The reasons for the change in attitude, from that of L'Ordene where knighthood is an order held in high regard, on a par with the clergy, to that of L'Apparicion, where it is seen as corrupted and failing in its duties, may be looked for in the crusaders' defeat at Nicopolis, which had been inflicted on them just before Bovet penned his work. In this respect, L'Apparicion shares characteristics with its contemporary works, just like L'Ordene does with works of its time.